Effect of continued feeding of cows' milk on asymptomatic infants with milk protein sensitive enteropathy - Iyngkaran, N.; Yadav, M.; Boey, C.G.; Lam, K.L. (BMJ Publishing Group, 1988)
The clinical response and the histological changes in the mucosa of the small bowel in response to continued feeding with cows' milk protein were assessed over a period of 2-6 weeks in 24 infants who had shown histological changes without immediate clinical symptoms after challenge with a diet containing cows' milk protein. Twenty of the 24 infants (83%) thrived well on cows' milk protein. Jejunal biopsy specimens taken six to eight weeks after the initial biopsy showed histological improvement in all 20 infants compared with biopsy specimens taken soon after the challenge, which had shown mucosal damage. The mucosa had returned to normal in 12, was mildly abnormal in seven, and moderately abnormal in one. Corresponding improvements in the activities of mucosal enzymes were seen. In four of the 24 infants (17%) symptoms developed between three and six weeks. Histological examination of the jejunal biopsy specimens showed that mucosal damage had progressed in two, and remained the same in two; moreover, the disaccharidase activities remained depressed. The present study shows that most infants with enteropathy caused by sensitivity to cows' milk protein but without clinical symptoms develop tolerance to the protein and the mucosa returns to normal despite continued feeding with cows' milk protein.